Komparasi Kurikulum Pendidikan Lingkungan Negara Maju dan Negara Berkembang: Sebuah Kajian Literatur - Fatria, Erian; Priadi, Agus; Apriyanti, Eka; Daikoban, Damianus; Yuniasih, Idah (UNM Environmental Journals, 2024)
Based on the facts of environmental education in Finland and China, it can be seen that the development of environmental education curriculum in Finland and China can both be said to be very advanced. The government strongly supports environmental education programs in Finland, the goal is to equip Finnish people with knowledge of environmental issues and be able to become citizens who have netizenship behavior towards the environment and responsible environmental behavior. While the Chinese government supports the field of environmental education and sustainable development education so that the Chinese population can practice environmental protection and be more aware of the surrounding environment that has been degraded. We can certainly use this as an example in implementing the environmental education curriculum in our country, so that our environment can be saved from crisis to achieve sustainability as expected by the SDG's